Corrosion behavior of titanium in response to sulfides produced by Porphyromonas gingivalis. Issue 2 (February 2018) - Harada, Rino; Kokubu, Eitoyo; Kinoshita, Hideaki; Yoshinari, Masao; Ishihara, Kazuyuki; Kawada, Eiji; Takemoto, Shinji
Graphical abstract: Highlights: No siginificant differences in color change and no progression of oxidation was indicated in tes media regardless of sulfide content. No significant levels of titanium release was indicated in any of the test mediums. Sulfide and sulfate were found on titanium specimens placed in sulfide containing mediums. Volatile sulfur compounds released from periodonpathic bacteria did not cause titanium corrosion over the immersion period of 14 days. Abstract: Objective: To investigate the effects of sulfides produced by Porphyromonas gingivalis ( P. gingivalis ) on the corrosion behavior of titanium. Methods: Commercially pure titanium disks were mirror-polished and immersed in culture medium (BHI), spent medium after culturing P. gingivalis (BHI-S), and culture medium with P. gingivalis (BHI-P), and incubated aerobically at 37 °C for 3–14 days. Titanium corrosion was evaluated through surface observation (using scanning electron microscope: SEM), color change (ΔE*ab), glossiness (Gs(20°)), chemical composition and state (using X-ray photoelectron spectroscopy: XPS), and titanium release. Results: ΔE*ab and Gs(20°) did not significantly differ among specimens placed in test mediums for the study duration (p > 0.05). SEM images of specimens showed no signs of localized or overall corrosion. XPS analysis indicated showed clear titanium metal state peaks on all specimens in addition to sulfide and sulfate on BHI-S and BHI-P specimens. Valency fraction of titanium decomposed from Ti2p spectrum of BHI-S and BHI-P specimens indicated no progression of oxidation. No significant levels of titanium release were found regardless of the mediums' sulfide content. Results suggested that sulfides produced by P. gingivalis attached on the surface of titanium specimens but did not cause titanium corrosion over the immersion period of 14 days. Significance: It is imperative for dental practitioners to be aware of any elements which may influence the clinical success of titanium implants.